Pathogenesis of dental fluorosis: biochemical and cellular mechanisms - Gina Alejandra Castiblanco-Rubio; Stefania Martignon-Biermann; Jaime Eduardo Castellanos-Parra; Wilson Alfonso Mejía-Naranjo (Universidad de Antioquia, 2017)
The mechanisms involved in the development of dental fluorosis are still unknown. The development of in vivo and in vitro models using biologically relevant concentrations of fluoride for the emergence of fluorosis has allowed suggesting hypotheses that contribute to the understanding of the mechanisms that produce this defect in enamel development, with high prevalence in Colombia. This topic review presents an update on the normal mechanisms of the formation of enamel and how they are affected by exposure to high concentrations of fluoride. This is a thorough review of the deleterious effects of fluoride on the cells and the extracellular matrix, especially during the maturation stage, resulting in a delay of the removal of the protein matrix of amelogenins, as well as the appearance of mottled enamel-a characteristic of dental fluorosis. Finally, it shows the perspectives of the study of this defect in enamel development from biochemistry and cellular and molecular biology.